PARP inhibitor‐based treatment in metastatic, castration‐resistant prostate cancer (mCRPC): A systematic review and meta‐analysis - Michela Roberto; Mattia Alberto Di Civita; Daniele Marinelli; Andrea Torchia; Nertila Cara; Giulia Maltese; Iolanda Speranza; Daniele Santini (BJUI Compass)
Abstract Background We present a systematic review and meta‐analysis of randomized clinical trials (RCTs) with PARPi either as monotherapy or in combination with an androgen receptor‐targeted agent (ARTA) in first‐ and second‐line settings. Methods Primary endpoints are radiographic progression free survival (rPFS) and overall survival (OS) in patients with mCRPC and either unselected, homologous recombination repair wild‐type (HRR−), homologous recombination repair mutated (HRR+) or with BRCA1, BRCA2, or ATM mutation. The effect of PARPi + ARTA in the second‐line setting is also explored. Safety is a secondary end‐point. Results A total of five phase III (first line: MAGNITUDE, PROpel, TALAPRO‐2; second line: PROfound, TRITON3) and two phase II RCTs (second line: NCT01972217, NCT01576172) were selected. In the first‐line setting, rPFS was significantly improved in PARPi + ARTA arm in all comers (HR 0.70, p < 0.00001), HRR− (HR 0.76, p = 0.005), HRR+ (HR 0.57, p = 0.0003), and BRCA1/2‐mutated patients (HR: 0.33, p < 0.00001). OS was improved in the population with HRR+ status (HR 0.76, p = 0.02) but not statistically significant in BRCA1/2‐mutated patients (HR 0.57, 95% CI 0.30–1.08, p = 0.08). In the second line, PARPi improves rPFS (HR for BRCA2 0.31, p = 0.002) and OS (HR for BRCA1/2 0.71, p = 0.01) only in such patients. In this setting, no advantage was reported by adding a PARPi to an ARTA. The arm with PARPi either as monotherapy or in combination with ARTA showed a significantly higher toxicity profile. Conclusions PARPi‐based therapy represents a compelling treatment option for HRR+ mCRPC, mainly BRCA1/2‐mutated patients. However, further biomarker analysis are needed in order to identify other responsive patients across the different disease settings.